A Protocol on Effect of Cryotherapy and Myofascial release Technique in Calf Muscle Spasticity of Spastic Diplegic Cerebral Palsy Children - Priya J. Tikhile; Ashish W. Bele (Indian Journal of Forensic Medicine & Toxicology, 2021)
Background: Cerebral Palsy is been one of the developmental disorders affecting the infants brain. Themost common form of Cerebral Paralysis being Spastic Cerebral Palsy affects children functionally andprevents their social functioning. Most of the physiotherapy interventions to treat spasticity are Cryotherapy,Myofascial Release technique. Cryotherapy is effective in reducing Spasticity and some suggest MyofascialRelease Technique is also effective in reducing spasticity. Aim: To find out the effect of Cryotherapy andMyofascial Release Technique in calf muscle of Spastic Diplegic Cerebral Palsy Children. Methods: 30Participants with Spastic Diplegia will be selected on the basis of inclusion as well as exclusion criteria. Thepatients will be evaluated using Modified Ashworth Scale and Modified Tardieu Scale for calf muscle priorto the treatment. The 30 participants will be divided into 3 groups. All the groups will receive Cryotherapy,MFR technique and combined effect of both the techniques separately. The patients will be again evaluatedafter the treatment by using MSA and MTS. Conclusion: This Study Concluded that there may be significantreduction in calf muscle spasticity in spastic diplegic cerebral palsy children by using combine effect of bothCryotherapy and Myofascial Release technique ore one of the method.